O lirismo como instrumento de intervenção política: uma análise da obra Os poemas possíveis, de José Saramago - Santos, Antonio Tiago Lopes dos (2024)
In countries that have faced periods of exception under the yoke of fascist governments, where authoritarianism and censorship replaced democracy and silenced opposition, the artistic class has always represented the primary dissenters. In this context, the strong repression of dissenters by these regimes required caution from artists who expressed opposition to the barbarism of the time through veiled criticism, merely suggested, with the aim of safeguarding themselves from the severe repression of the prevailing political system. In this context, this dissertation aims to analyze the work Os poemas possíveis by the Alentejo writer José Saramago, published in 1966, during the decade when censorship and repression intensified in Portugal, with the objective of investigating the techniques employed by the poet to prompt reflection in readers about the abuses of the Oliveira Salazar dictatorship, which lasted for more than four decades in the country. The analysis, focusing on the iconography and imagery contained in the poems, seeks to establish relationships between the symbolism present in the work and the historical-political context of the country during its production and publication, through the comparison of the various allegories, metaphors, and other visual elements found in the poems, suggesting a possible critical relationship between the author's political stance and the democratic crisis faced by the country. It is assumed that the appeal to this technique may foster a desire for transformation and promote an articulation among critical readers towards an awakening of consciences alienated by Portuguese Estado Novo indoctrination. To this end, this research relies on the theoretical assumptions of scholars of Saramago's work, such as Horácio Costa (1997), Maria Alzira Seixo (1999), Elielson Sgarbi (2013), and Fernângela Silva (2018); Salazarism theorists such as Marcos Maurício Costa Freitas (2020), Lincoln Ferreira Secco (2004) and Figueiredo (1976); as well as authors who discuss neorealist poetry, such as Josyane Nascimento (2012), Eduardo Lourenço (2007) and Irene Pimentel (2011).